2019
DOI: 10.1177/2050312119832093
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication in patients with type 2 diabetes mellitus: Multicenter prospective observational study

Abstract: Objective: To compare Helicobacter pylori ( H. pylori ) eradication rate of type 2 diabetic patients with non-diabetic subjects. Methods: In this multicenter prospective observational study, H. pylori -infected subjects were enrolled from three university-affiliated hospitals. Eradication regimen was triple therapy with standard dose of proton pump inhibitors (b.i.d), amoxicillin (1.0 g b.i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…15,16 Other studies revealed disagreement in the prevalence between H. pylori infection in diabetics and non-diabetics 21.3% vs. 20.2%, 17 42.9% vs. 43.1%, 18 73.5% vs. 76.5%. 19 This study contradicts our results which may be attributed to the inconsistent measurements used for H. pylori positivity, IgG antibodies were used to define infection in most studies. IgG antibodies reflect prior infection, but are not sensitive indicators of current infection.…”
Section: Discussioncontrasting
confidence: 93%
“…15,16 Other studies revealed disagreement in the prevalence between H. pylori infection in diabetics and non-diabetics 21.3% vs. 20.2%, 17 42.9% vs. 43.1%, 18 73.5% vs. 76.5%. 19 This study contradicts our results which may be attributed to the inconsistent measurements used for H. pylori positivity, IgG antibodies were used to define infection in most studies. IgG antibodies reflect prior infection, but are not sensitive indicators of current infection.…”
Section: Discussioncontrasting
confidence: 93%
“…In fact, our study provides evidence for this possibility by comparing the HbA1c level in eradication success diabetics and failure ones, and better glycemic control was found in diabetes succeed in H. pylori eradication compared with those diabetics failed in treatment (Figure h), which means diabetics with poor glycemic control have a higher risk of failure than better glycemic one. The study of Nam et al 38 also suggested that HbA1c (⩾7.5%) was a significant factor predicting H. pylori eradication in T2DM. Considering the limited number of studies analyzing whether glycemic control affects H. pylori eradication, our results need to be validated by more clinic trials.…”
Section: Discussionmentioning
confidence: 92%
“…The main characteristics of the studies included were shown in Table 1. In all studies included, 11 prospective studies compared the H. pylori eradication rate in diabetes and non‐diabetes 29‐39 . Eleven retrospective studies compared the proportion of diabetes and other clinic factors (age, gender, smoking, drinking, overweight, peptic ulcer disease, blood pressure, and history of NSAIDS) in groups failed and succeed in H. pylori eradication 40‐50 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason could be due to a small number of PM (only four poor metabolisers) involved in this study which made interpretation difficult. The patients from the PM group were smokers 19 and comorbid with diabetes mellitus 20 which might influence on eradication despite poor metaboliser status. As additional finding of our study, alcohol drinkers and betel chewers got higher eradication rate than non-drinkers and non-betel chewer but that were not statistically significant.…”
Section: Characteristicsmentioning
confidence: 99%